Chapter 6: Drug Information Resources (Foundations in Clinical Pharmacy Practice, 2025)
AuthorMr. Sri Venkatesh Uriti, Associate Professor, Department of Pharmacology, Sri Sivani College of Pharmacy, Etcherla, Srikakulam, Andhra Pradesh, IndiaAbstractReviewing the complex and vast pharmaceutical information requires mastery of diverse resources and retrieval methodologies essential for evidence-based practice. Primary literature evaluation encompasses journal article analysis, preprint assessment, and clinical trial interpretation with emphasis on methodological quality, bias identification, and applicability determination. Secondary resources provide synthesized information through systematic reviews, meta-analyses, and evidence summaries offering comprehensive evaluations of therapeutic approaches with structured quality assessment. Electronic databases facilitate efficient information retrieval through specialized platforms including PubMed, Embase, and Cochrane Library, each requiring specific search strategies and controlled vocabulary mastery. Clinical decision support tools integrate patient-specific data with medication knowledge bases through computerized alerts, order sets, and interactive applications supporting point-of-care decisions. Information retrieval skills combine systematic search strategy development, resource selection based on question type, critical evaluation of conflicting information, and effective communication of complex findings to various audiences. This detailed approach enables pharmacists to address medication information needs with accuracy, efficiency, and clinical relevance while navigating information overload and evaluating source credibilityKeywords: Biomedical Literature, Information Retrieval, Evidence Synthesis, Clinical Databases, Knowledge ManagementVIEW PDF